Acute exacerbations of progressive-fibrosing interstitial lung diseases. (21st December 2018) - Kolb, Martin; Bondue, Benjamin; Pesci, Alberto; Miyazaki, Yasunari; Song, Jin Woo; Bhatt, Nitin Y.; Huggins, John T.; Oldham, Justin M.; Padilla, Maria L.; Roman, Jesse; Shapera, Shane
Acute exacerbation of interstitial lung disease (ILD) is associated with a poor prognosis and high mortality. Numerous studies have documented acute exacerbation in idiopathic pulmonary fibrosis (IPF), but less is known about these events in other ILDs that may present a progressive-fibrosing phenotype. We propose defining acute exacerbation as an acute, clinically significant respiratory deterioration, typically less than 1 month in duration, together with computerised tomography imaging showing new bilateral glass opacity and/or consolidation superimposed on a background pattern consistent with fibrosing ILDs. Drawing on observations in IPF, it is suspected that epithelial injury or proliferation and autoimmunity are risk factors for acute exacerbation in ILDs that may present a progressive-fibrosing phenotype, but further studies are required. Current acute exacerbation management strategies are based on recommendations in IPF, but no randomised controlled trials of acute exacerbation management have been performed. Although there are no formal strategies to prevent the development of acute exacerbation, possible approaches include antifibrotic drugs (such as nintedanib and pirfenidone), and minimising exposure to infection, airborne irritants and pollutants. This review discusses the current knowledge of acute exacerbation of ILDs that may present a progressive-fibrosing phenotype and acknowledges limitations of the data available. Acute exacerbation can occur in ILDs associated with a progressive-fibrosing phenotype, other than IPF; and are associated with significant morbidity. There are pressing needs to identify patients at risk of AE and for therapies that reduce this risk. http://ow.ly/tEA330mNE0r